Pengaruh Kerusakan Jalan Terhadap Kinerja Jalan (Studi Kasus : Jalan SM. Amin Kota Pekanbaru) - Karizal Karizal; M. Yusa; Elianora Elianora (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
SM. Amin road is a national road with two lane two way undivided road (2/2 UD) type in Pekanbaru. Many heavy vehicles pass this road, thus making damage in SM. Amin road especially in Sta 7+400 – Sta 7+600. The road damage will have an impact on the road performance which is decreasing. The aims of this research are to identify the type of damage and to compare road performance in road segment (road with damage and un-damage) by using Indonesian Highway Capacity Manual (MKJI) 1997 method. The conclusion on this research are: (1) the type of damage that greatly affects the decrease in speed is delamination (2) Degree of Saturation in both road segment is 0.71 that mean the road still proper to use, the delay in SM. Amin road caused by the damage on the road. (3) The average speed of road segment in damage and un-damage road is 20km/hours and 29km/hours respectively. (4) The level of service for road segment in un-damage road is in C level category, and D level category for damage road.Keywords: Road Damage, Road Performance, Level Of Service